2022
DOI: 10.1007/s40747-022-00705-w
|View full text |Cite
|
Sign up to set email alerts
|

A federated learning framework for cyberattack detection in vehicular sensor networks

Abstract: Vehicular Sensor Networks (VSN) introduced a new paradigm for modern transportation systems by improving traffic management and comfort. However, the increasing adoption of smart sensing technologies with the Internet of Things (IoT) made VSN a high-value target for cybercriminals. In recent years, Machine Learning (ML) and Deep Learning (DL) techniques attracted the research community to develop security solutions for IoT networks. Traditional ML and DL approaches that operate with data stored on a centralize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Multiple performance criteria, such as accuracy, precision, recall, F1-score, and training duration, were used to evaluate the proposed model. The testing results showed that the suggested FL method effectively detects attacks while protecting users' anonymity within VSNs [83].…”
Section: Analysis Of Federated Learning Based Existing Work In Iot Ne...mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple performance criteria, such as accuracy, precision, recall, F1-score, and training duration, were used to evaluate the proposed model. The testing results showed that the suggested FL method effectively detects attacks while protecting users' anonymity within VSNs [83].…”
Section: Analysis Of Federated Learning Based Existing Work In Iot Ne...mentioning
confidence: 99%
“…In 2022, Maha Driss et.al have developed FL-based system for the detection of cyberattack in Vehicular Sensor Networks (VSNs) [83]. To guarantee efficient attack detection, an ensembler unit is employed in conjunction with a set of GRU models.…”
Section: Analysis Of Federated Learning Based Existing Work In Iot Ne...mentioning
confidence: 99%
“…The model consists of two convolutional layers and three fully connected dense layers, which can improve performance and reduce computing power. Driss et al [25] proposed an attack detection framework for vehicle sensor networks based on federated learning. The scheme uses a group of gated recursive units and a signal group unit based on a random forest.…”
Section: Related Workmentioning
confidence: 99%
“…By comparing this value with the existing related protocol described in Tables 7 and 8. The proposed method requires low communication cost than (Alexopoulos et al, 2018;Driss et al, 2022). According to Table 8, a distributed system has allowed the federated learning model to reach less computation process than the other classical methods.…”
Section: Computational Overheadmentioning
confidence: 99%
“…The host and network intrusion detection systems with blockchain technology in a detailed manner (Driss et al, 2022). The authors forecasted the usage of blockchain architecture in detecting the malicious nodes in huge CIDS networks and different categories of algorithms used in blockchain have been detailed and studied by Salam Al‐E'mari et al (2022).…”
Section: Related Workmentioning
confidence: 99%